2008
DOI: 10.1088/0022-3727/41/10/105503
|View full text |Cite
|
Sign up to set email alerts
|

VUV spectroscopic properties of rare-earth (RE3+= Eu, Tb, Tm)-dopedAZr2(PO4)3(A+= Li, Na, K) type phosphate

Abstract: The excitation spectra of pure and rare-earth (RE3+ = Eu, Tb, Tm)-doped AZr2(PO4)3 (A+ = Li, Na, K) in the vacuum ultraviolet (VUV) regions are investigated. The results indicate that these samples show strong absorption in the VUV range. The band ranging from 130 to 160 nm is due to the absorption band of host lattice or PO4 groups; the band at 160–200 nm is related to the charge transfer (CT) transition of O–Zr. For Eu3+-doped samples, the weak band in the excitation spectra at about 208 nm is related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…[14][15][16] Thus, some of this NASICON type materials were found to be good hosts for novel luminescent materials. The VUV luminescence properties of RE 3+ -doped AZr 2 (PO 4 ) 3 (A + = Li, Na, K) [17] [5] were demonstrated as novel potential blue luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[14][15][16] Thus, some of this NASICON type materials were found to be good hosts for novel luminescent materials. The VUV luminescence properties of RE 3+ -doped AZr 2 (PO 4 ) 3 (A + = Li, Na, K) [17] [5] were demonstrated as novel potential blue luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…-group in structure of NASICON structure exhibits great VUV luminescence properties, [17] ions via electrochemical lithium insertions. [7] Chemical lithiation using nBu-Li (2.5 m in hexane) at room temperature is better for Eu 2+ -doped luminescent materials synthesis and research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VUV studies of zirconium containing phosphors like ZrP 2 O 7 , CaZr(PO 4 ) 3 and NaZr 2 (PO 4 ) 3 have been investigated by Kaneyoshi [8]. Recently Zhi-Jun Zhang et al reported the preparation of Tb 3+ doped AZr 2 (PO 4 ) 3 by solid-state reactions at high temperature with feasibility as a green phosphor of PDP, which can be easily excited by 172 nm [9].…”
Section: Introductionmentioning
confidence: 99%